A parametric distance and its application to find the nearest approximation of a fuzzy number. (2015) - Amirfakhrian, Majid
In this paper, we propose a new approach to compute distance between fuzzy numbers. This new distance, is a meter on the set of all fuzzy numbers with continuous left and right spread functions. By using this metric we approximate a parametric fuzzy number with a polynomial parametric one.